The impact of magnesium biotinate and arginine silicate complexes on metabolic dysfunctions, antioxidant activity, inflammation, and neuromodulation in high-fat diet-fed rats - Şahin, Kazım; Sahin, Emre; Orhan, Cemal; Er, Besir; Akoglan, Bayram; Ozercan, Ibrahim Hanifi; Komorowski, James R. (Springer-Verlag Italia Srl, 2024)
Biotin and arginine play crucial roles in lipid metabolism and may offer promising interventions against obesity. This study examined the combined effect of magnesium biotinate (MgB) and inositol-stabilized arginine silicate complex (ASI) on obesity-related oxidative imbalance, inflammation, lipid metabolism and neuromodulation in rats on a high-fat diet (HFD). Forty rats were divided into five groups: (a) control: rats were fed a standard diet containing 12% of energy from fat; (b) HFD: rats were fed the HFD with 42% of energy from fat; (c) HFD + MgB: rats were fed the HFD and given 0.31 mg/kg body weight (BW) MgB, (d) HFD + ASI: rats were fed the HFD and were given 12.91 mg/kg BW ASI), and (e) HFD + MgB + ASI: rats were fed the HFD and given 0.31 mg/kg BW MgB and 12.91 mg/kg BW ASI). The combined administration of MgB and ASI reduced the levels of serum cholesterol, free fatty acid (FFA), and malondialdehyde (MDA), as well as liver inflammatory cytokines, sterol regulatory element-binding protein 1-c (SREBP-1c), and 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) proteins (P < 0.001) compared to HFD rats without supplementation. Moreover, this combination increased the activities of antioxidant enzymes (P < 0.05) and boosted the brain-derived neurotrophic factor (BDNF), serotonin, dopamine (P < 0.001), as well as liver insulin receptor substrate 1 (IRS-1) and peroxisome proliferator-activated receptor gamma (PPAR-gamma) (P < 0.001). These findings suggest that combining MgB and ASI could deter liver fat accumulation and enhance lipid metabolism in HFD-fed rats by modulating various metabolic pathways and neuromodulators related to energy metabolism. This combination demonstrates potential in addressing obesity and its related metabolic dysfunctions.
Keywords: Biotin; Arginine; High-fat diet; Neuromodulators; Energy metabolism